4 Predictors of ventricular arrhythmia identified from follow up of tetralogy of fallot. (30th September 2020) - Kelly, B; Brennan, PF; Lockhart, C; Spence, M; Owens, C; Sands, A; McCrossan, B; Gordon, J; Briggs, L
Abstract : Introduction: Tetralogy of Fallot (TOF) is the most common cyanotic congenital heart defect. Subsequent to the introduction of surgical repair, long-term outcomes for patients with TOF have improved significantly. However right ventricular outflow tract dysfunction and regurgitative volume overload remains a recognised sequalae, often progressing to right ventricular (RV) dilatation and dysfunction, arrhythmia, and premature death. In repaired TOF (rToF), QRS prolongation is a recognised predictor of the development of sustained ventricular tachycardia (VT) and sudden cardiac death. Ventricular dysfunction, atrial tachyarrhythmias and RV hypertrophy are also predictive of sustained VT and death in rToF. We, retrospectively, report the overall long-term survival of rToF from our single tertiary centre. Methodology: For all 229 consecutive patients with TOF, baseline clinical characteristics, echocardiography and magnetic resonance imaging results, documented evidence of arrhythmia and analysis of outcomes were collected retrospectively using Northern Ireland Electronic Care Record (NIECR) and our dedicated in-hospital databases. Causes of death were elicited using NIECR +/or the patients primary care physician. We analysed all-cause mortality as well as cardiovascular mortality. Cardiovascular mortality was subsequently divided into sudden cardiac/arrhythmic death and expected cardiac death. Additionally, we analysed the incidence of confirmed ventricular arrhythmia defined as ³3 consecutive ventricular complexes. Survival was estimated using Kaplan-Meier analysis. Univariate predictors of sudden cardiac death (SCD) or the occurrence of ventricular events (VE) during follow-up were assessed via binary logistic regression and a Cox proportional hazards model. Clinically predictors on univariate analysis, based on an α-level <0.01, were subsequently imputed into a multivariate model. Results: The mean patient age was 34 ±11 years (range 16–68 years) and 57% (n=131) are male. 6.1% (n=14) patients have died from all-causes during follow-up. Of the 14 deaths, SCD occurred in 50% (n=7) patients, expected cardiac death in 21% (n=3) patients, and non-cardiovascular causes accounted for the remaining 29% (n=4) patients. The median survival estimate was 65 years age (95% C.I 61.02–68.98). ECG-documented or device captured ventricular events occurred in 11% (n=26) patients during follow-up. On univariate analysis, the presence of late gadolinium enhancement (LGE) scar on CMR (p<0.005, OR 18.20), LVEF<50% (p<0.005, OR 7.21), QRS>160 ms (p 0.01, OR 3.12) and AF (p 0.02, OR 4.66) were all associated with increased odds of VE. In the multivariate model both impaired LV systolic function (LVEF<50%, p 0.04, HR 5.63) and late gadolinium enhancement (LGE) scar on CMR (p <0.005, HR 11.42) were significant predictors of VE during follow-up, as summarised in table 1 . Conclusion: Amongst patients with rToF, presence of LGE scar on CMR, QRS>160 ms, LVEF<50% and AF are associated with increased occurrence of ventricular events. These findings represent a contemporary cohort of ToF patients and whilst have been described previously, add weight to the potential for risk scoring algorithms in ToF to prevent sudden death.